QIZILQUMNING NUKUS QUMI HUDUDIDA KATTA QUM SICHQONINING MAVSUMIY SON DINAMIKASI - Yesimbetov R.M., Yesimbetov R.M.; Xabibullayev A.J., Xabibullayev A.J.; Shadenova B.U, Shadenova B.U; Ametov M. M., Ametov M. M. (Actual problems and prospects of the study of the fauna, 2024)
In northwestern Kyzylkum of the Republic of Karakalpakstan, with a densely populated arable zone of Karakozak districts, Nukus Qumi district on three sides, Nukus City on the Northwest and West, Takhakopir, Karakozak districts on the North, Ellikkal'a districts on the south, in the Western Kyzylkum districts of the Fourkul district, the year-year-year scarcity of the dushki sandpikers has a climate and dehydrated negative effect on them.